Social support as a factor of mental health in wartime conditions: Communication and interaction - Kostruba, Natalia S.; Kostruba, Andrii (My University, 2024)
According to researchers, social support is a powerful tool for maintaining a person's mental health. The aim of this study was to empirically identify the relationship between social support as a resource and the stability of an individual's mental health in wartime conditions. The following methods were used in the study: “The Mental Health Continuum – Short Form” (E.L. Nosenko, A.H. Chetveryk-Burchak), and the BASIC Ph Model. Mathematical-statistical methods applied included correlation analysis with the determination of the Pearson correlation coefficient (r) and the determination of differences using the Student's t-test. The study sample consisted of 382 Ukrainians living in Ukraine (of which 116 were men and 266 were women), with an average age of 21.3 years (ranging from 18 to 43 years). The results obtained demonstrate that more than a third of the respondents have a low level of stability of mental health, which is interpreted as a state of depression, a tense psycho-emotional state, passivity in activity and interaction with others. To overcome this state, the respondents most often resort to cognitive skills, belief and physical activity. Analysis of the relationship between mental health stability and various forms of social support revealed that communication and interaction with friends, family members, and members of organisations or communities to which one belongs are associated with higher indicators of mental health and well-being. Differences in mental health indicators and the use of social support were also found between men and women. Men are less likely to use social support as a method of coping with difficult life circumstances. The obtained data do not exhaust the problem of studying social support as a factor of mental health in wartime conditions, but they confirm that communication and interaction are associated with the psychological health and well-being of the individual
Keywords: mental health; psychological well-being; hedonic well-being; social well-being; social support; psychological resources